Philosophie und Mystagogie: Karl Rahners "reductio in mysterium" als Prinzip seines Denkens - Fischer, Klaus P. (Zeitschrift für katholische Theologie, 1998)
In our times, both investigators and critics of Rahner's philosophical and theological thought are mostly neglecting or underestimating the influence of Heidegger on Rahner. This is even the case for Richard Schaeffler, one of the most outstanding Christian philosophers of Germany, who has just reached 70 years of age. In his works, Schaeffler shows, for example, the all pervading importance of Heidegger's thought for theological thinking. He also analyzes shrewdly the potentialities of the transcendental method as applied by Rahner. Yet, there are many more links between Rahner's thought - even theological and Heidegger's: not only the Heidegger of his first work "Sein und Zeit", but also the Heidegger after the tum ("Kehre"), when he particularly payed attention to the "mystery" of "Being" and of the human existence. The presumed relationship between Heidegger and Rahner does not imply that Rahner's theology is derived from Heidegger's philosophy, but points out a spiritual affinity as well as a similar method and fashion of thinking. The fabric of Rahner's affinity to Heidegger appears evidently in an early Innsbruck seminar on "mystery", even more than in many of his famous later writings. These early papers have never been published, but are preserved in a small number of manuscripts, produced from private recordings. The focus of that seminar appears to have been the following: the Mystery of God, though constantly evading, is yet appearing, by opening a space for its apparition in the apex of the human being, which could be called our "transcendence" or "ecstasis". Moreover, Rahner's affinity to Heidegger means that his own thinking basically holds much more of a historical perspective than could have been expected considering his Marechalian point of departure. In addition, Rahner's indebtedness to Heidegger breathes through his new reception, as well as synthetic translation, of the Church's mystical tradition, which lies at the very base of his theology.